2019
DOI: 10.5539/ijsp.v8n6p91
|View full text |Cite
|
Sign up to set email alerts
|

Sex Preference, Religion and Ethnicity Roles in Fertility Among Women of Childbearing Age in Nigeria: Examining the Links Using Zero-Inflated Poisson Regression Model

Abstract: The study aimed at examining the independent and joint influence of three cultural factors; religion, sex preference (SP) and ethnicity on fertility in Nigeria. Cross-sectional population-based cluster design approach was used for the study. The investigated population group was women of reproductive age (n=19,348). Probability of bearing ≥5 children, refined Total Fertility Rate and mean fertility were used to assess fertility. Data were analyzed using demographic and Zero-Inflated Poisson models. Fert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Thus, the national estimate of mCEB was inflated by the Hausa/Fulani Muslim childbearing practices. These findings are consistent with the outcome of studies conducted among Nigerian women [ 11 , 12 ]. Strong adherence to the tenets of religious and ethnic groups in Nigeria may be a possible reason for our findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the national estimate of mCEB was inflated by the Hausa/Fulani Muslim childbearing practices. These findings are consistent with the outcome of studies conducted among Nigerian women [ 11 , 12 ]. Strong adherence to the tenets of religious and ethnic groups in Nigeria may be a possible reason for our findings.…”
Section: Discussionsupporting
confidence: 92%
“…Time spent on schooling and contraceptive adoption are other possible explanations for this difference. The higher fertility found among Igbo Christians than Yoruba Muslim men in monogamous families cannot be isolated from a high preference for a male child and low uptake of modern contraceptives among the Igbo ethnic group [ 10 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…By ethnic group classifi cation, the Hausa/Fulani had the highest TFR (8.4), while Muslim women had the highest TFR (7.8) compared to other religious groups. While the Hausa/Fulani women were recorded as the group with higher TFR, this was followed by Igbo women compared to the Yoruba women (Ayo Stephen et al 2019). Also, among the southeast Nigerian states, Enugu state (the location of Eha-Amufu) is one of the states in the region with higher TFR (NDHS 2018); this is not unconnected with the mixed religion in the area and proximity to a high fertility region (North Central) and the state with highest TFR in the region of the southeast (Ebonyi state).…”
Section: Background: Fertility Rate In Nigeria and The Role Of Womenmentioning
confidence: 93%
“…Meanwhile, a study by Ayo Stephen et al (2019), which focused on the three major ethnic groups in Nigeria, revealed the unseen, complex nature of fertility rates in Nigeria in connection with other variables. According to their fi ndings, the combination of the current TFR of the Igbo, Yoruba and Hausa/Fulani refi ned is 6.3.…”
Section: Background: Fertility Rate In Nigeria and The Role Of Womenmentioning
confidence: 99%
“…In Nigeria, many factors such as ethnicity, religion, education, age at first birth e.t.c. have been identified as fertility predictors [43]. However, in practice, no single factor can explain the fertility behavior of a particular country [17].…”
Section: Introductionmentioning
confidence: 99%